Collaborative Governance and Emergency Management: A Case Study of Latvia - Beinaroviča, Ieva Daniela (Socialiniai tyrimai, 2016)
Emergencies – crises, disasters and catastrophes – cannot be managed by individuals or one organization, collaborative actions are needed In the context of this paper, a two-part research on collaborative governance and emergency management in Latvia has been carried out. This research is important because due to extreme weather conditions even “safe” countries should be able to deal with frequently recorded emergencies. It also contributes to the literature on emergency management in the context of Europe. The method of a case study was employed for this qualitative research seeking to clarify the situation and provide answers to the research question. The research showed that much attention is being given to coordinating emergency management systems in Latvia. The new Civil Defence and Disaster Management Law is the legal basis for collaborative actions but it should be amended to ensure not only formal but also practical collaboration.